2017
DOI: 10.2147/ijn.s148487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cancer cell migration with CuS@mSiO<sub>2</sub>-PEG nanoparticles by repressing MMP-2/MMP-9 expression

Abstract: The metastasis of cancer cells is a vital aspect of disease progression and therapy. Although a few nanoparticles (NPs) aimed at controlling metastasis in cancer therapy have been reported, the NPs are normally combined with drugs, yet the direct therapeutic effects of the NPs are not reported. To study the direct influence of NPs on cancer metastasis, the potential suppression capacity of CuS@mSiO 2 -PEG NPs to tumor cell migration, a kind of typical photothermal NPs, was systemically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…4b-d). O'Hara R, and Tamamoto T et al had reported that SAA was involved in adhesion, migration, and tissue infiltration of inflammatory cells, induced matrix metalloproteinases which could interact with degrading extracellular matrix (ECM) controlling the diffusion and migration of cells [30][31][32][33][34][35]. Possible mechanisms of SAA for stimulating MMP-9 might be via formyl peptide receptor like-1-mediated signaling [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…4b-d). O'Hara R, and Tamamoto T et al had reported that SAA was involved in adhesion, migration, and tissue infiltration of inflammatory cells, induced matrix metalloproteinases which could interact with degrading extracellular matrix (ECM) controlling the diffusion and migration of cells [30][31][32][33][34][35]. Possible mechanisms of SAA for stimulating MMP-9 might be via formyl peptide receptor like-1-mediated signaling [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…4b-d). O'Hara R, and Tamamoto T et al had reported that SAA was involved in adhesion, migration, and tissue in ltration of in ammatory cells, induced matrix metalloproteinases which could interact with degrading extracellular matrix (ECM) controlling the diffusion and migration of cells [25][26][27][28][29][30]. Possible mechanisms of SAA for stimulating MMP-9 might be via formyl peptide receptor like-1-mediated signaling [31].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al created copper monosulfide nanocrystals modified with mesoporous silica and PEGylation (CuS@mSiO 2 -PEG). They found a reduction in the metastasis of cancer cells and improved survival rates after subcutaneous injections of HeLa cells that were prestimulated with Cus@mSiO 2 -PEG NPs in comparison with those of cells that were prestimulated with free copper in a HeLa lung metastasis model [138], demonstrating that NPs enhance therapeutic efficacy. Further studies have focused on a new target enzyme candidate, lysyl oxidase (LOX), which is elevated in the TME.…”
Section: Modulation Of Enzymes/cytokines In the Tmementioning
confidence: 98%
“…Accordingly, MMPs have been investigated for preventing and treating tumors; however, the delivery of MMP inhibitors has been challenging due to poor specificity. Recent studies have shown the use of NPs with potential MMP inhibitors to control metastasis in cancer therapy [138,139]. For example, Wang et al created copper monosulfide nanocrystals modified with mesoporous silica and PEGylation (CuS@mSiO 2 -PEG).…”
Section: Modulation Of Enzymes/cytokines In the Tmementioning
confidence: 99%